PENGARUH SALES PROMOTION, KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA PT ELANG DWI MITRA - Hendi, Hendi; Rustam, Triana Ananda (LPPM Universitas Putera Batam, 2021)
Customer loyalty is become a very important role in a company. Customer loyalty can be effect by various aspects towards a company. PT Elang Dwi Mitra has a lot of issue due to their lack of latest offers, late on delivery, customer is not satisfied with what they are receive and etc. This research has the purpose to find out how the effect of sales promotion, service qualtiy and customer satisfaction on customer loyalty at PT Elang Dwi Mitra. The sample to be used is saturated sampling of 112 respondents. This study is used SPSS version 25 to processing the data and also used distributing questionnaires as the data collection technique. Based on the result that sales promotion has a positive and insignificant effect on customer loyalty toward PT Elang Dwi Mitra. While service quality and customer satisfaction both have a positive and significant effect on customer loyalty toward PT Elang Dwi Mitra. Simultaneously that sales promotion, service quality and customer satisfaction have a positive and significant effect on customer loyalty toward PT Elang Dwi Mitra.